DEEP STRUCTURE AND MECHANICAL BEHAVIOR OF THE LITHOSPHERE IN THE HANGAI-HöVSGöL REGION, MONGOLIA: NEW CONSTRAINTS FROM GRAVITY MODELING - Petit C.; Déverchère J.; San'kov V.; Fairhead D.; Calais E. (My University, 2002)
We investigate the deep structure and mechanical behavior of the lithosphere beneath the Hangai–Hövsgöl region, central Mongolia, Asia, in order to explain the origin and support of large-scale doming in this deforming area. We propose a gravity- and topography-based model which accounts for constraints provided by other independent results from xenolith and tomography studies. Deviations of the measured gravity from the theoretical Airy-compensation model are examined. A long-wavelength low-gravity anomaly is spatially correlated with low pressure and shear velocity anomalies in the mantle, and with the extent of Cenozoic volcanic outcrops. We interpret it as a deep-seated low-density asthenosphere and model its effect on the Bouguer gravity signal using a 600 km wide light asthenospheric body (density reduction −10 kg m−3) located between 100 and 200 km. North and south of the Hangai–Hövsgöl dome, short-wavelength highs and lows in the Bouguer gravity field are clearly correlated with fault activity. They seem to reflect opposite senses of flexure of a rigid lithosphere across two major active faults, the Sayan and Bogd transpressional systems, and are modeled by Moho deflections of 10 and 5 km, respectively. Finally, a short-wavelength (200 km), high-amplitude (−50 mGal) gravity residual remains beneath the highest part of the mountain bulge, namely the Hangai dome. Based on previously published xenolith analyses, we interpret it as an anomalous, low-density body which may represent underplated cumulates or mafic granulites at the uppermost mantle. We conclude that upper mantle dynamics necessarily play an important role in the origin and evolution of the Hangai–Hövsgöl dome, but without requiring significant thinning of the lithosphere.
Keywords: topography; gravity methods; Mongolia; Hangay Mountains; upper mantle; flexure